Abordagens alternativas para medicação intracanal: avaliação in vitro de complexos de prata(I) e revisão de escopo sobre produtos naturais de origem vegetal - Amancio, Breno Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
As medicações intracanais (MICs) tradicionalmente utilizadas, como o hidróxido de cálcio e as pastas antibióticas, apresentam limitações relevantes, incluindo eficácia reduzida frente a micro-organismos associados a infecções endodônticas persistentes, citotoxicidade dependente da concentração e potencial indução de resistência bacteriana. Nesse contexto, a busca por alternativas antimicrobianas eficazes e biologicamente seguras tem impulsionado a investigação de MICs alternativas, como complexos metálicos de prata(I) e produtos naturais. Publicação 1 - O objetivo foi avaliar a atividade antimicrobiana dos complexos de prata(I) com os ligantes probenecida (Ag-PROB), furosemida (Ag-FSE) e ácido 4-aminobenzóico (Ag-pABA) frente a Candida albicans e Enterococcus faecalis, bem como a sua citotoxicidade sobre células da papila apical humana (hAPCs). A síntese e caracterização dos complexos foram confirmadas por FTIR. A atividade antimicrobiana foi analisada por meio da determinação da concentração inibitória mínima (CIM), teste de difusão em ágar e pela análise do metabolismo de biofilmes por AlamarBlue. A viabilidade/metabolismo das hAPCs foi determinada pelo ensaio de AlamarBlue. Duas formulações de pasta triantibiótica (TAP), compostas por metronidazol, ciprofloxacino e minociclina, preparadas a partir de comprimidos/cápsulas (TC) ou de antibióticos grau United States Pharmacopeia (USP), foram utilizadas como controles. Os complexos de prata(I) apresentaram atividade antimicrobiana frente a E. faecalis e C. albicans, enquanto TAP TC e TAP USP exibiram halos de inibição apenas para E. faecalis. Em biofilmes, Ag-PROB, Ag-FSE e Ag-pABA promoveram maior redução da atividade metabólica de ambos os micro-organismos em comparação às TAPs (p < 0,05). Os complexos de prata(I) foram mais citotóxicos do que as TAPs. Publicação 2 - O objetivo foi identificar e sintetizar, por meio de revisão de escopo, as evidências científicas sobre o uso de produtos naturais como MIC no tratamento endodôntico de dentes permanentes. Foram incluídos na revisão 78 estudos experimentais e ensaios clínicos que investigaram produtos naturais como MICs em dentes permanentes. Houve predomínio de estudos in vitro e ex vivo, com foco principal na avaliação da atividade antimicrobiana, especialmente frente a E. faecalis. Os produtos naturais mais investigados foram própolis, Aloe vera (babosa), Azadirachta indica (neem) e Curcuma longa (cúrcuma), os quais apresentaram atividade antimicrobiana, em parte dos estudos, comparável às MICs convencionais, além de apresentarem perfis de biocompatibilidade favoráveis. Entretanto, os resultados mostraram-se heterogêneos e dependentes do modelo experimental empregado. Alguns produtos também apresentaram efeitos de preservação das propriedades mecânicas da dentina e potencial anti-inflamatório. Em relação à Publicação 1, concluiu-se que os complexos de prata(I) Ag-PROB, Ag-FSE e Ag-pABA apresentaram atividade antimicrobiana superior sobre E. faecalis e C. albicans em comparação às formulações TAP TC e TAP USP. No entanto, esses complexos foram mais citotóxicos do que as TAPs. Na Publicação 2 conclui-se que os produtos naturais apresentam potencial para serem utilizados como MIC; entretanto, a heterogeneidade de resultados e a escassez de ensaios clínicos limitam sua indicação clínica.

Intracanal medicaments (MICs) traditionally used, such as calcium hydroxide and antibiotic pastes, present important limitations, including reduced efficacy against microorganisms associated with persistent endodontic infections, concentration-dependent cytotoxicity, and the potential induction of bacterial resistance. In this context, the search for effective and biologically safe antimicrobial alternatives has driven the investigation of new MICs, including silver(I) metal complexes and natural products. Publication 1 - The objective was to evaluate the antimicrobial activity of silver(I) complexes with the ligands probenecid (Ag-PROB), furosemide (Ag-FSE) and 4-aminobenzoic acid (Ag-pABA) against Candida albicans and Enterococcus faecalis, as well as their cytotoxicity on human apical papilla cells (hAPCs). The synthesis and characterization of the complexes were confirmed by FTIR. Antimicrobial activity was assessed through determination of the minimum inhibitory concentration (CIM), agar diffusion assay, and analysis of biofilm metabolism using AlamarBlue. The viability/metabolism of hAPCs was determined by the AlamarBlue assay. Two triple antibiotic paste formulations (TAP), composed of metronidazole, ciprofloxacin, and minocycline, prepared from tablets/capsules (TC) or from United States Pharmacopeia grade antibiotics (USP), were used as controls. The silver(I) complexes exhibited antimicrobial activity against E. faecalis and C. albicans, whereas TAP TC and TAP USP showed inhibition halos only against E. faecalis. In biofilms, Ag-PROB, Ag-FSE, and Ag-pABA promoted a greater reduction in the metabolic activity of both microorganisms compared with TAPs (p < 0,05). The silver(I) complexes were more cytotoxic than the TAPs. Publication 2 - The objective was to identify and synthesize, through a scoping review, the scientific evidence regarding the use of natural products as MIC in the endodontic treatment of permanent teeth. The review included 78 experimental studies and clinical trials investigating natural products as MICs in permanent teeth. A predominance of in vitro and ex vivo studies was observed, mainly focused on antimicrobial activity, especially against E. faecalis. The most investigated natural products were própolis, Aloe vera (babosa), Azadirachta indica (neem), and Curcuma longa (cúrcuma), which demonstrated antimicrobial activity, in part of the studies, comparable to conventional MICs, in addition to favorable biocompatibility profiles. However, the results were heterogeneous and dependent on the experimental model employed. Some products also showed preservation effects on dentin mechanical properties and anti-inflammatory potential. Regarding Publication 1, it was concluded that the silver(I) complexes Ag-PROB, Ag-FSE, and Ag-pABA exhibited superior antimicrobial activity against E. faecalis and C. albicans compared with TAP TC and TAP USP formulations; however, these complexes were more cytotoxic than TAPs. In Publication 2, it was concluded that natural products show potential to be used as MIC; however, the heterogeneity of results and the scarcity of clinical trials limit their clinical indication.Intracanal medicaments (MICs) traditionally used, such as calcium hydroxide and antibiotic pastes, present important limitations, including reduced efficacy against microorganisms associated with persistent endodontic infections, concentration-dependent cytotoxicity, and the potential induction of bacterial resistance. In this context, the search for effective and biologically safe antimicrobial alternatives has driven the investigation of new MICs, including silver(I) metal complexes and natural products. Publication 1 - The objective was to evaluate the antimicrobial activity of silver(I) complexes with the ligands probenecid (Ag-PROB), furosemide (Ag-FSE) and 4-aminobenzoic acid (Ag-pABA) against Candida albicans and Enterococcus faecalis, as well as their cytotoxicity on human apical papilla cells (hAPCs). The synthesis and characterization of the complexes were confirmed by FTIR. Antimicrobial activity was assessed through determination of the minimum inhibitory concentration (CIM), agar diffusion assay, and analysis of biofilm metabolism using AlamarBlue. The viability/metabolism of hAPCs was determined by the AlamarBlue assay. Two triple antibiotic paste formulations (TAP), composed of metronidazole, ciprofloxacin, and minocycline, prepared from tablets/capsules (TC) or from United States Pharmacopeia grade antibiotics (USP), were used as controls. The silver(I) complexes exhibited antimicrobial activity against E. faecalis and C. albicans, whereas TAP TC and TAP USP showed inhibition halos only against E. faecalis. In biofilms, Ag-PROB, Ag-FSE, and Ag-pABA promoted a greater reduction in the metabolic activity of both microorganisms compared with TAPs (p < 0,05). The silver(I) complexes were more cytotoxic than the TAPs. Publication 2 - The objective was to identify and synthesize, through a scoping review, the scientific evidence regarding the use of natural products as MIC in the endodontic treatment of permanent teeth. The review included 78 experimental studies and clinical trials investigating natural products as MICs in permanent teeth. A predominance of in vitro and ex vivo studies was observed, mainly focused on antimicrobial activity, especially against E. faecalis. The most investigated natural products were própolis, Aloe vera (babosa), Azadirachta indica (neem), and Curcuma longa (cúrcuma), which demonstrated antimicrobial activity, in part of the studies, comparable to conventional MICs, in addition to favorable biocompatibility profiles. However, the results were heterogeneous and dependent on the experimental model employed. Some products also showed preservation effects on dentin mechanical properties and anti-inflammatory potential. Regarding Publication 1, it was concluded that the silver(I) complexes Ag-PROB, Ag-FSE, and Ag-pABA exhibited superior antimicrobial activity against E. faecalis and C. albicans compared with TAP TC and TAP USP formulations; however, these complexes were more cytotoxic than TAPs. In Publication 2, it was concluded that natural products show potential to be used as MIC; however, the heterogeneity of results and the scarcity of clinical trials limit their clinical indication.
Alternative approaches for intracanal medication: in vitro evaluation of silver(I) complexes and a scoping review of plant-derived natural products
Keywords: Endodontia regenerativa; Medicamento fitoterápico; Compostos de prata; Regenerative endodontics; Regenerative endodontics; Phytotherapeutic drugs; Silver compounds; Root canal therapy